Subsidiary model of the government social services regulation: its possible use in Kazakhstan - Tusupova, Leila; Grechko, Tetyana (Skhid, 2014)
This article discusses the nature and content of subsidiary model of state regulation of the social sphere and the possibility of its use in the Republic of Kazakhstan. Model of state paternalism, in which should be a massive and comprehensive support of the living standards of the population due to the state’s resources, has exhausted itself and is not compatible with market principles. Defines the principles of vicarious model of state regulation of the social sphere: prevention; social investment; interactivity; tolerance. The conditions of the subsidiary model of state regulation of the social sphere: transparency; openness; continuity and intensity of positive information space; public competition; contractual partnership. Matched procedural elements of interaction that will determine the nature of the practical implementation of the proposed ideological principles, namely, target-oriented approach; expert and assessment activities; contests; nontax incentive mechanisms; meeting site; social contract. Established economic and legal mechanisms and organizational solutions subsidiary structural model of state regulation of social services, such as community foundations. The principles, conditions and procedural elements, economic and legal mechanisms and organizational solutions subsidiary structural model of state regulation of social services allow us to determine the possibility of transition from a paternalistic model to subsidiary for the Republic of Kazakhstan. This means accessible and free to all citizens of basic social services, especially education and health; redistribution of state social spending in favor of the most vulnerable, while reducing assistance provided to families; reduce social inequalities; provide citizens with the highest possible level of social consumption from its own revenues. The need to achieve this transition imposes extremely stringent requirements for economic growth. The main task in this way- providing high perspective, and most importantly, sustainable economic development.